Seed and pollen dispersal and fine-scale spatial genetic structure of a threatened tree species: Pericopsis elata (HARMS) Meeuwen (Fabaceae) - Angbonda, D.M.A.; Monthe, F.K.; Bourland, N.; Boyemba, F.; Hardy, Olivier J. (Springer, 2021)
Seed and pollen dispersal are important for defining sustainable forest management practices. By reducing population density, selective logging could affect not only the seed production of timber species but also the selfing rate and the patterns of seed and pollen rains. To assess these risks, we characterized seed and pollen dispersal patterns and the fine-scale spatial genetic structure (FSGS) of Pericopsis elata, a gregarious, wind-dispersed legume tree which is highly logged in Central Africa and threatened by overexploitation. Eleven microsatellite markers were used to genotype 189 adults and 664 seedlings in a 4 km2 plot in the Democratic Republic of Congo (DRC). According to the neighbourhood model, seed dispersal was extremely leptokurtic, with 80% of seeds dispersal distances <75 m, 15% >500 m. Pollen dispersal was locally more extensive (median distance 260 m), but pollen immigration was not detected, and the selfing rate (54%) appeared particularly high compared to other tropical tree species. Limited gene dispersal resulted in remarkably high FSGS (Sp = 0.072). A decay of inbreeding with age also suggests that the species is prone to inbreeding depression. The reproductive success of trees was positively related to their diameter at breast height (dbh), with half of the progeny mothered by trees with dbh > 97 cm and fathered by trees with dbh > 119 cm. Our study highlights that (1) seed sources must be diversified for plantation or population reinforcement to limit consanguinity, and (2) the legal minimum cutting diameter in DRC (60 cm) should be increased to maintain enough post-logging reproductive potential.